Water harvesting in sub-Saharan Africa - Critchley, W.; Gowing, J. (CTA / Routledge, 2012)
There is an urgent need – heightened by climate change – for appropriate technologies to address the problems of variable rainfall, frequent drought and low water productivity in Sub-Saharan Africa. By managing and increasing the quantity of water on farmers’ fields (water harvesting), agricultural yields can be increased and livelihoods improved. The approaches described in this valuable text include small-scale systems that collect, store and make use of local surface runoff for agriculture.